2014
DOI: 10.1055/s-0034-1376927
|View full text |Cite
|
Sign up to set email alerts
|

Die S3-Leitlinie zur Diagnostik und Therapie der Zwangsstörungen

Abstract: Die erste deutschsprachige evidenz- und konsensbasierte S3-Leitlinie zur Diagnostik und Therapie der Zwangsst?rungen verfolgt das Ziel, die Versorgung der betroffenen Patienten zu verbessern und die Entscheidungsgrundlage f?r die Berufsgruppen zu optimieren, die an der Behandlung und Betreuung von Personen mit Zwangs?st?rungen beteiligt sind. Sie umfasst nicht nur Empfehlungen zur Diagnostik und Therapie, sondern soll diese auch f?r Betroffene und ihre ?Angeh?rigen transparent machen, um ihnen eine weitgehend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The results of the pilot study served to revise the MCT-OCD, and this revised version will be evaluated in a randomized controlled trial with an outpatient sample in the proposed study, which may allow more robust conclusions about the efficacy of the intervention. The MCT-OCD in a group format comes with the general advantages of group therapy (e.g., patients are able to share their thoughts with others who have similar symptoms and obstacles), which has already been shown to be very helpful for patients with OCD for CBT groups [51].…”
Section: Metacognitive Training For Patients With Ocdmentioning
confidence: 99%
“…The results of the pilot study served to revise the MCT-OCD, and this revised version will be evaluated in a randomized controlled trial with an outpatient sample in the proposed study, which may allow more robust conclusions about the efficacy of the intervention. The MCT-OCD in a group format comes with the general advantages of group therapy (e.g., patients are able to share their thoughts with others who have similar symptoms and obstacles), which has already been shown to be very helpful for patients with OCD for CBT groups [51].…”
Section: Metacognitive Training For Patients With Ocdmentioning
confidence: 99%
“…It has a lifetime prevelence of about 1.3% (Fawcett et al, 2020) and often takes a chronic course if untreated (van Oudheusden et al, 2018). Cognitive behavioral therapy (CBT) with exposure and response prevention (ERP) and pharmacotherapy with serotonin‐reuptake inhibitors are recommended in national and international guidelines (Kordon et al, 2014; National Institute for Health and Care Excellence [NICE], 2005). However, in clinical practice, ERP is often not used (Böhm et al, 2008; Külz et al, 2010) or incorrectly applied (Gillihan et al, 2012; Hipol & Deacon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first-line psychological treatment is cognitive-behavioral therapy (CBT) with exposure and response prevention (Ex/RP; Skapinakis et al, 2016), which has shown to be effective with large effect sizes (Hedges' g = 1.31; Öst et al, 2015). Group settings are increasingly recommended to serve the high number of patients and reduce treatment costs (Kordon et al, 2014;Sousa et al, 2006). A recent metaanalysis (Schwartze et al, 2016) showed that group CBT for OCD was as effective as individual therapy and pharmacotherapy and superior to wait-list control (Hedges' g = 0.97, 95% CI 0.58; 1.37, p < .001, k = 4).…”
Section: Introductionmentioning
confidence: 99%